Гносеологічні аспекти технічного регулювання забезпечення якості продукції - Большаков, В. Б.; Косач, Н. І.; Павлова, Г. О.; Чернишенко, О. В.; Bolshakov, Volodymyr; Kosach, Nataliia; Pavlova, Ganna; Chernyshenko, Olexandr (Видавництво Львівської політехніки, 2019)
Останнім часом у світі все більше уваги приділяється одній із основних складових конкурен- тоспроможності продукції – її якості. Це зумовлено тим, що, враховуючи глобалізацію та відкритість ринків, на світовий ринок потрапляє все більша кількість різноманітної продукції і її якість виходить на перший план. До цього також спонукає доступність її вибору і вимогливість споживачів. Якість продукції можна охарактеризувати як сукупність нормованих властивостей продукції, які задовольняють певні потреби споживачів стосовно її цільового призначення й умов використання. Тому є всі підстави констатувати, що якість продукції визначається мірою співвідношення фактично досягнутого показника якості до його нормованого значення, яке сформовано запитами споживачів, вимогами стандартів, договорів, контрактів, і якщо вона є мірою, то її необхідно виміряти, визначити ступінь її відповідності. В Україні одним з основних дієвих інструментів забезпечення якості будь-якої продукції визнана гармонізована з європейською Система технічного регулювання. Для забезпечення її функціонування прийнято низку національних нормативних актів і гармонізованих міжнародних стандартів, мета яких – впровадження у систему технічного регулювання прозорої конструктивної методології підтвердження якості продукції за допомогою оцінювання її відповідності встановленим вимогам.

In recent times, in the world, more attention is paid to one of the main components of the competitiveness of products – its quality. This is due to the globalization and openness of the markets, an increasing number of diverse products. This also prompts the availability of its choice and demanding consumers. The concept of quality - the most important consumer characteristics of products, determined by the ability to satisfy customers, as well as predictable and unexpected effects on the relevant stakeholders, encompasses not only their functions and characteristics, but also their perceived value and benefit for the customer. That is, the quality of products can be characterized as a set of normalized properties of products that satisfy certain consumer needs in relation to its intended purpose and conditions of application. Therefore, there is every reason to state that the quality of products is determined by the ratio of its actually achieved quality index to its normalized value, which is formed by the requests of customers, requirements of standards, contracts, contracts, and if it is a measure, then it should be measured , the degree of its conformity is determined. In Ukraine, one of the main effective tools for the product quality assurance is recognized, as harmonized with the European system of Technical Regulation. It is based on the legal regulation of relations in the area of definition, establishment, application and implementation of mandatory requirements for product characteristics and related processes and methods. A number of national normative acts and harmonized international standards have recently been adopted in Ukraine, aiming the introduction of transparent constructive methodology for the verification of product quality in the system of technical regulation, which constitutes the process of proving that the specified requirements. Modules for assessing the conformity of products, or regulated by the relevant regulatory documents, in particular technical regulations, or which must pay particular attention, are determined by the manufacturer. Realization of this methodology will lead the Ukrainian state to satisfy the needs of consumers and to solve economic problems.
Epistemological aspects of technical regulation of providing production quality
Keywords: метрологічне підтвердження; оцінювання відповідності; продукція; процес вимірювання; технічне регулювання; якість продукції; Metrological confirmation; Conformity assessment; Production; Measurement process; Technical regulation; Product quality